Family Visit with Frances Kamp - Watkins, Howard::::::::: (1979)
Fred Marsden, Christine Watkins, friend Jeannie Marsden holding Adam Watkins in Fran's front yard 329 Rolling Hills Avenue, San Mateo, CA